The temperature dependence of the helical twist of DNA - Kriegel, Franziska; Matek, Christian; Dršata, Tomáš; Kulenkampff, Klara; Tschirpke, Sophie; Zacharias, Martin; Lankaš, Filip; Lipfert, Jan (Nucleic acids research, 2018)
DNA is the carrier of all cellular genetic information and increasingly used in nanotechnology. Quantitative understanding and optimization of its functions requires precise experimental characterization and accurate modeling of DNA properties. A defining feature of DNA is its helicity. DNA unwinds with increasing temperature, even for temperatures well below the melting temperature. However, accurate quantitation of DNA unwinding under external forces and a microscopic understanding of the corresponding structural changes are currently lacking. Here we combine single-molecule magnetic tweezers measurements with atomistic molecular dynamics and coarse-grained simulations to obtain a comprehensive view of the temperature dependence of DNA twist. Experimentally, we find that DNA twist changes by ΔTw(T) = (-11.0 ± 1.2)°/(°C·kbp), independent of applied force, in the range of forces where torque-induced melting is negligible. Our atomistic simulations predict ΔTw(T) = (-11.1 ± 0.3)°/(°C·kbp), in quantitative agreement with experiments, and suggest that the untwisting of DNA with temperature is predominantly due to changes in DNA structure for defined backbone substates, while the effects of changes in substate populations are minor. Coarse-grained simulations using the oxDNA framework yield a value of ΔTw(T) = (-6.4 ± 0.2)°/(°C·kbp) in semi-quantitative agreement with experiments.
Keywords: simulace molekulární dynamiky; konformace nukleové kyseliny; denaturace nukleových kyselin; Magnetic Fields; Nucleic Acid Conformation; Temperature; Molecular Dynamics Simulation; Nucleic Acid Denaturation; Computer Simulation; DNA; teplota; magnetické pole; počítačová simulace